Modulating Function-Based Leak Detection, Size Estimation and Localization for a Water Pipe Prototype - Rubmann, J.; Noack, M.; Reger, J.; Pérez-Zuñiga, G. (Institute of Electrical and Electronics Engineers, 2024)
We propose a new method for leak detection and localization in water pipes based on a mathematical model that describes the flow dynamics by two coupled linear first order hyperbolic partial differential equations. Using the modulating function approach, a system of auxiliary PDEs is derived and solved in order to obtain appropriate modulating functions. This allows estimating the leak size and the leak position, resorting to algebraic I/O equations only. For this purpose, no spatial discretization of the PDE model is needed. The theoretical results are validated with experimental data from a water pipe prototype and the performance of the proposed approach is evaluated in comparison to an existing late lumping model-based leak detection system.
Keywords: Leak detection; Leak; Function (biology); Computer science; Estimation; Environmental science; Engineering; Environmental engineering; Systems engineering; https://purl.org/pe-repo/ocde/ford#2.11.04